Local vs. Regional Groundwater Flow Delineation from Stable Isotopes at Western North America Springs. Issue 1 (20th July 2016) - Springer, Abraham E.; Boldt, Elizabeth M.; Junghans, Katie M.
Abstract: The recharge location for many springs is unknown because they can be sourced from proximal, shallow, atmospheric sources or long‐traveled, deep, regional aquifers. The stable isotope ( 18 O and 2 H) geochemistry of springs water can provide cost‐effective indications of relative flow path distance without the expense of drilling boreholes, conducting geophysical studies, or building groundwater flow models. Locally sourced springs generally have an isotopic signature similar to local precipitation for that region and elevation. Springs with a very different isotopic composition than local meteoric inputs likely have non‐local recharge, representing a regional source. We tested this local vs. regional flow derived hypothesis with data from a new, large springs isotopic database from studies across Western North America in Arizona, Nevada, and Alberta. The combination of location‐specific precipitation data with stable isotopic groundwater data provides an effective method for flow path determination at springs. We found springs in Arizona issue from a mix of regional and local recharge sources. These springs have a weak elevation trend across 1588 m of elevation where higher elevation springs are only slightly more depleted than low elevation springs with a δ 18 O variation of 5.9‰. Springs sampled in Nevada showed a strong elevation‐isotope relationship with high‐elevation sites discharging depleted waters and lower elevation springs issuing enriched waters; only a 2.6‰ difference exists in 18 O values over an elevation range of more than 1500 m. Alberta's springs are mostly sourced from local flow systems and show a moderate elevation trend of 1200 m, but the largest range in δ 18 O, 7.1‰. Abstract : Article Impact Statement : A cost‐effective and simple method for delineating the source areas of springs with stable isotopes is developed and demonstrated.